A diagnostic evaluation of a molecular assay used for testing and treating anorectal chlamydia and gonorrhoea infections at the point-of-care in Papua New Guinea. (May 2019) - Badman, S.G.; Willie, B.; Narokobi, R.; Gabuzzi, J.; Pekon, S.; Amos-Kuma, A.; Hakim, A.J.; Weikum, D.; Gare, J.; Silim, S.; Guy, R.J.; Donovan, B.; et al.
Abstract: Objectives: Papua New Guinea has among the highest prevalences of sexually transmissible infections (STIs) globally with no services able to accurately test for anorectal Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections. Here we prospectively evaluated the diagnostic performance of a molecular CT/NG assay used at the point-of-care (POC) with the aim of enhancing anorectal STI screening and same-day treatment. Methods: Men who have sex with men, transgender women and female sex workers taking part in Papua New Guinea's first large-scale biobehavioural study were enrolled and asked to provide a self-collected anorectal swab for POC GeneXpert CT/NG testing. Same-day treatment was offered if positive. A convenience sample of 396 unique and randomly selected samples were transported to Australia for comparison using the Cobas 4800 CT/NG test (Roche Molecular Diagnostics, Pleasanton, CA, USA). Results: A total of 326 samples provided valid results by Cobas whereas 70 samples provided invalid results suggesting inhibition. The positive, negative and overall percentage agreements of GeneXpert CT/NG for the detection of C. trachomatis were 96.7% (95% CI 92.3%–98.9%), 95.5% (95% CI 91.3%–98.0%) and 96.0% (95% CI 93.3%–97.8%), and for N. gonorrhoeae were 93.0% (95% CI 86.1%–97.1%), 100.0% (95% CI 98.3%–100.0%) and 97.8% (95% CI 95.6%–99.1%), respectively. Conclusions: The overall rate of agreement between the GeneXpert and Cobas CT/NG assays was high with 96.0% for C. trachomatis and 97.8% for N. gonorrhoeae . Results from this study data suggest that the GeneXpert CT/NG assay is suitable for testing self-collected anorectal specimens at the POC and that same-day treatment was feasible.